The Romantic tradition and the fantastic short story in Macedonian literature - Капушевска-Дракулевска, Лидија (Poznańskie Studia Slawistyczne, 2011)
The fantastic short story in Macedonian literature has developed along lines typical for fantastic literature in general; through the folklore collections made by Marko Cepenkov, it leads to modern artistic literature, thus accomplishing a synthesis of tradition and innovation of its own. There are numerous authors in Macedonian literature who are admirers of the fantastic short story as a form of literary narration within the frameworks of fiction. Some typical forms of traditional romantic fantastic short stories could be found in the literary work of Macedonian writers: Slavko Janevski, Vlada Urošević, Mitko Madzunkov,  Krste  Čačanski,  Dimitrie  Duracovski,  Dragi  Mihajlovski, Aleksandar Prokopiev, Venko Andonovski, etc. The popularity of fantastic short stories in Macedonian literature has not diminished over time; on the contrary, it has gained intensity. The fantastic short story tries to retain the polymorphism of eyes’ and souls’ visions. In the very name of Romanticism, therefore, we can say that: “Romanticism is not dead!”.